Double-Layer Flexible Neural Probe With Closely Spaced Electrodes for High-Density in vivo Brain Recordings - Pimenta, Sara; Rodrigues, José A.; Machado, Francisca; Ribeiro, João F.; Maciel, Marino J.; Bondarchuk, Oleksandr; Monteiro, Patricia; Gaspar, João; Correia, José H.; Jacinto, Luis (Frontiers in Neuroscience, 2021)
Flexible polymer neural probes are an attractive emerging approach for invasive brain recordings, given that they can minimize the risks of brain damage or glial scaring. However, densely packed electrode sites, which can facilitate neuronal data analysis, are not widely available in flexible probes. Here, we present a new flexible polyimide neural probe, based on standard and low-cost lithography processes, which has 32 closely spaced 10 µm diameter gold electrode sites at two different depths from the probe surface arranged in a matrix, with inter-site distances of only 5 µm. The double-layer design and fabrication approach implemented also provides additional stiffening just sufficient to prevent probe buckling during brain insertion. This approach avoids typical laborious augmentation strategies used to increase flexible probes’ mechanical rigidity while allowing a small brain insertion footprint. Chemical composition analysis and metrology of structural, mechanical and electrical properties demonstrated the viability of this fabrication approach. Finally, in vivo functional assessment tests in the mouse cortex were performed as well as histological assessment of the insertion footprint, validating the biological applicability of this flexible neural probe for acquiring high quality neuronal recordings with high signal to noise ratio (SNR) and reduced acute trauma.